2015
DOI: 10.1111/aec.12320
|View full text |Cite
|
Sign up to set email alerts
|

Comparative dietary ecology of two congeneric marsupial folivores

Abstract: Knowledge of species diets is critical to assisting our understanding of their ecology. Using microhistological analysis of faecal samples, we described and compared the diets of sympatrically occurring folivorous congenerics, common and mountain brushtail possums (Trichosurus vulpecula and T. cunninghami, respectively). Throughout the 28-month study period, common brushtails relied heavily on eucalypt foliage, particularly very young leaves, which is consistent with data from captive studies on their dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…In contrast, few tall genera (> 2.5 m height) were available compared to shrubs and annuals, but their frequency of occurrence within scats was high. This suggests that possums spend more time foraging in the canopy than on the ground, a result supported by previous studies of possum foraging and movement, where diet is dominated by canopy species (Foulkes, 2001; Cruz et al, 2012; Gloury & Handasyde, 2016). This could be a result of the avoidance of predators at ground level, the quality of food in the canopy, or a combination of both.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast, few tall genera (> 2.5 m height) were available compared to shrubs and annuals, but their frequency of occurrence within scats was high. This suggests that possums spend more time foraging in the canopy than on the ground, a result supported by previous studies of possum foraging and movement, where diet is dominated by canopy species (Foulkes, 2001; Cruz et al, 2012; Gloury & Handasyde, 2016). This could be a result of the avoidance of predators at ground level, the quality of food in the canopy, or a combination of both.…”
Section: Discussionsupporting
confidence: 78%
“…Although other studies have suggested that possum diet changes seasonally, most studies have not spanned > 12 months (Freeland & Winter, 1975; Fitzgerald, 1984; Statham, 1984; Cruz et al, 2012). In one exception, differences were found between the wet and dry season diet of brushtail possums in the tropics, with some sex effects also observed over the 29 month study period (Gloury & Handasyde, 2016). Although these studies suggest that the post-release dietary acclimatization in our study could have included some seasonal effects, more long-term dietary studies are needed to differentiate between normal fluctuations in possum diet and post-release effects.…”
Section: Discussionmentioning
confidence: 99%